Sterubin: Enantioresolution and Configurational Stability, Enantiomeric Purity in Nature, and Neuroprotective Activity in Vitro and in Vivo. Issue 32 (15th May 2020) - Hofmann, Julian; Fayez, Shaimaa; Scheiner, Matthias; Hoffmann, Matthias; Oerter, Sabrina; Appelt‐Menzel, Antje; Maher, Pamela; Maurice, Tangui; Bringmann, Gerhard; Decker, Michael
Abstract: Alzheimer′s disease (AD) is a neurological disorder with still no preventive or curative treatment. Flavonoids are phytochemicals with potential therapeutic value. Previous studies described the flavanone sterubin isolated from the Californian plant Eriodictyon californicum as a potent neuroprotectant in several in vitro assays. Herein, the resolution of synthetic racemic sterubin (1 ) into its two enantiomers, ( R )‐1 and ( S )‐1, is described, which has been performed on a chiral chromatographic phase, and their stereochemical assignment online by HPLC‐ECD coupling. ( R )‐1 and ( S )‐1 showed comparable neuroprotection in vitro with no significant differences. While the pure stereoisomers were configurationally stable in methanol, fast racemization was observed in the presence of culture medium. We also established the occurrence of extracted sterubin as its pure ( S )‐enantiomer. Moreover, the activity of sterubin (1 ) was investigated for the first time in vivo, in an AD mouse model. Sterubin (1 ) showed a significant positive impact on short‐ and long‐term memory at low dosages. Abstract : The Californian plant Eriodictyon californicum produces the flavanone sterubin as its ( S )‐enantiomer. Fast racemization takes places in cell culture medium, whereas configurational stability was observed in methanol. Sterubin was a potent neuroprotectant in vitro and displayed significant beneficial effects on short‐ and long‐term memory in an AD mouse model.